Reproductive Nutrition Education as a Preventive Measure Against Imbalanced Dietary Patterns and Malnutrition Risks among Adolescent Girls - Mutalazimah Mutalazimah; Dyah Intan Puspitasari; Siti Zulaekah; Nur Lathifah Mardiyati; Farida Nur Isnaeni; Setia Asyanti; Khayla Febriannisa'; Adelia Triana Putri; Magistra Ammar Alghifari (Jurnal Ilmiah Pengabdian Masyarakat Bidang Kesehatan (Abdigermas), 2026)
Background of study: Indonesian adolescent girls face a triple burden of malnutrition: anemia, undernutrition, and obesity. Driven by poor nutritional literacy and eating disorders, these issues threaten long-term reproductive health. This community service program aims to provide reproductive nutrition education and measure the nutritional status of 40 adolescent girls at SMA Batik 1 Surakarta. Methods: The knowledge variable was measured using a 22-item instrument regarding reproductive nutrition with proven validity and reliability, while the nutritional status variable was determined using the body mass index (BMI) formula following weight and height measurements. The educational activity was conducted using a booklet containing reproductive nutrition materials, with the following time breakdown: preparation and opening (10 minutes), pretest (25 minutes), educational session using a reproductive nutrition booklet (30 minutes), posttest (25 minutes), weight and height measurements (90 minutes), and discussion and closing (30 minutes). Result: Reproductive nutrition education significantly improved knowledge scores, with the average rising from 82.4 to 88.3 (p = 0.001). While average BMI measurements of adolescent girls remained within normal ranges, but individual data showed substantial variation, particularly in weight, which ranged widely from 35.70 kg to 83.00 kg. Conclusion: Continuous programs are essential to address the lack of reproductive nutrition knowledge and malnutrition to prevent imbalanced dietary patterns, fostering awareness and health readiness for adolescent girls as future mothers to ensure healthy future generations.